PANDANGAN ORANG JAWA TERHADAP KETAMPANAN DI DALAM KORPUS BAHASA JAWA - Enggartias Larasati; Novika Stri Wrihatni; Dwi Rahmawanto (Cross-border, 2023)
This research aimed to discover the concept of the word handsomeness in the perspective of Javanese people. The concept could be discovered by understanding the meaning of the word bagus based on its usage in the society. The data utilized to discover the meaning of bagus was obtained from the Javanese corpus in the corpus web application at https://korpus.ui.ac.id/. In the corpus web application, there is a data in which Javanese is utilized both from the oral and written sources since 1950 until 2010, approximately four million words. The meaning of bagus was discovered through collocation of the word’s meaning with another words. It refers to the concept of semantic preference. The words related with the word “bagus” was categorized based on the category of UCREL Semantic Analysis System (USAS). The research discovered that the word bagus is not only associated with a man with certain level of maturity, but also applies for kids and babies. Moreover, bagus is also associated with objects, animals, thoughts, personality, beliefs, and politeness. It discovers a new understanding to the concept of the word bagus in the Javanese society which is previously associated with the physical condition or a man’s look.